Support of Desi Cows in the daily livelihood of farm households in Karnataka - Kolekar, Dnyaneshwar; Chandre Gowda, M J; Sairam, C V (Indian Journal of Dairy Science, 2021)
Desi cows along with crossbred have major contribution in fulfilling the demand of milk by the growing population of India. Achieving food security, nutrition security and income security for the farmers and by the farmers is a priority concern of national and state governments in India. In order to fulfill the national goal of doubling farmers income by 2022, animal husbandry in general and dairy farming in particular are considered as potential activities. In this backdrop, the present study was carried out in six districts of Karnataka based on higher population of desi cows with a sample size of 240 farm households. The study revealed that the sample households had more number of milking desi cows as compared to crossbred cows. Average quantity of green fodder and concentrates fed per animal in case of desi cows was less compared to crossbred cows. Thus, total feed cost and expenditure per animal was less in case of desi cows than crossbred cows. Desi cows required less expenditure on health per day/anim., but the net return per animal, per farm and per liter was less in desi cows due to low productivity as compared to crossbred cows. Crossbred cows supplied more nutrients to farm i.e. NPK kg/year/animal compared to desi cows.Â  However, protein, fat and calcium nourishment per animal to the family was more in case of desi cows as compared to crossbred cows. Employment generation (Man days/year) per animal was more in case of crossbred cows as compared to indigenous cows. Security for uncertainties and status symbol was more in case of crossbred cows as compared to desi cows.